C‐Rel‐dependent monocytes are potent immune suppressor cells in cancer. Issue 4 (13th June 2022) - Li, Ting; Bou‐Dargham, Mayassa J.; Fultang, Norman; Li, Xinyuan; Pear, Warren S.; Sun, Honghong; Chen, Youhai H.
Abstract: Myeloid‐derived suppressor cells (MDSCs) are a heterogeneous population of leukocytes that are important for tumorigenesis and tumor immunotherapy. They comprise up to 10% of leukocytes in the blood of tumor patients and their depletion may be required for successful tumor immunotherapy. However, the identity of MDSCs remains obscure, primarily due to their heterogeneity and lack of a known lineage‐specific transcription factor specifying their differentiation. Using single‐cell transcriptomics and gene knockout approaches, we now describe a subset of murine and human myeloid suppressor cells, named rel‐dependent monocytes (rMos), which are programmed by the transcription factor c‐Rel of the NF‐κB family. Unlike MDSCs described previously, the c‐Rel‐dependent monocytes expressed a high amount of the proinflammatory cytokine IL‐1β together with a low level of suppressive molecule arginase 1. Both in vitro and in tumor‐bearing mice, these c‐Rel + IL‐1β hi Arg1 − monocytes promoted tumor growth by potently suppressing T cell function and showed a strong migratory phenotype, all of which were impaired by c‐Rel deficiency or inhibition. Mechanistic studies revealed that c‐Rel controlled the expression of monocyte signature genes through a unique transcriptional complex called the c‐Rel enhanceosome, and IL‐1β‐CCL2 crosstalk between tumor cells and the rel‐dependent monocytes maintained the suppressive tumor microenvironment. Thus, c‐Rel specifies the development of a suppressive monocyte population and could be selectively targeted for treating cancer. Graphical Abstract: Data to support: (i) c‐Rel‐dependent monocytes (rMos) are a new subset of myeloid suppressor cells with a unique set of markers; and (ii) the differentiation of rMos is specified by a lineage‐specific transcriptional complex called c‐Rel enhanceosome.